Ectopic expression of Hoxb4a in hemangioblasts promotes hematopoietic development in early embryogenesis of zebrafish. (December 2015) - Shu, Li‐Ping; Zhou, Zhi‐Wei; Zhou, Ting; Deng, Min; Dong, Mei; Chen, Yi; Fu, Yan‐Fang; Jin, Yi; Zhou, Shu‐Feng; He, Zhi‐Xu
Summary: Hemangioblast, including primitive hematopoietic progenitor cells, play an important role in hematopoietic development, however, the underlying mechanism for the propagation of hematopoietic progenitor cells remains elusive. A variety of regulatory molecules activated in early embryonic development play a critical role in the maintenance of function of hematopoietic progenitor cells. Homeobox transcription factors are an important class of early embryonic developmental regulators determining hematopoietic development. However, the effect of homeobox protein Hox‐B4 (HOXB4) ectopic expression on the development of hemangioblasts has not been fully addressed. This study aimed to investigate the role of Hoxb4a, an ortholog gene of HOXB4 in zebrafish, in the hematopoietic development in zebrafish. A transgenic zebrafish line was established with Cre‐loxP system that stably overexpressed enhanced green fluorescent protein (EGFP)‐tagged Hoxb4a protein under the control of hemangioblast‐specific lmo2 promoter. Overexpression of Hoxb4a in the development of hemangioblasts resulted in a considerable increase in the number of stem cell leukemia (scl) and lmo2 ‐positive primitive hematopoietic progenitor cells occurring in the posterior intermediate cell mass (ICM). Interestingly, Hoxb4a overexpression also disrupted the development of myelomonocytes in the anterior yolk sac and the posterior ICM, without affecting erythropoiesis in the posterior ICM. Taken together, these results indicate that Hoxb4a favours the development of hematopoietic progenitor cells originated from hemangioblasts in vivo .